Long-Term Hyperglycemia Impairs Hormonal Balance and Induces Oxidative Damage in Ovaries of Streptozotocin-Induced Diabetic Wistar Rat (Nigerian Journal of Physiological Sciences, 2020)
Reproductive dysfunction following insulin deficiency in Diabetes Mellitus has been well reported among diabetic patients. However, the mechanism through which Diabetes alters reproductive function remains oblivion. While most studies have focused on diabetes mellitus in male subjects, there have been cases on altered reproductive functions in females. These present study aims to investigate the effect of long term hyperglycemia on diabetic rats’ ovary. Female Wistar rats were assigned into control and diabetic group, each consisting of five animals. The later was induced with STZ (50mg/Kg intraperitoneal injection) and the animals were sacrificed after 14 weeks. The blood glucose, body and organ weight, serum hormone level along with oxidative stress parameters of the ovary and uterus were determined. Histology of the ovary and expression levels of CD79 in the ovary was also assessed. The weight of the diabetic rats after the experiment was significantly lower (p